Aging characteristics and self-healing properties of laser-textured superhydrophobic silicone rubber for composite insulators. (October 2021) - Chen, Lie; Guo, Fei; Yang, Tao; Hu, Tao; Bennett, Peter; Yang, Qibiao; Liu, Dun
Hightlights: The laser-textured silicone rubber surfaces have excellent anti-aging properties. The surface with a distinct hierarchical structure has better anti-aging properties. The laser-processed super-hydrophobic sample surface has self-healing performance. Low-molecular migration induces self-healing of hydrophobic surface microstructure. Abstract: The aging characteristics of laser-treated superhydrophobic silicone rubber surfaces was investigated through accelerated aging tests. It indicated that the superhydrophobic surfaces have excellent anti-aging properties, which is manifested in that even after aging for 1000 h, the contact angles of the superhydrophobic surfaces remain above 140 o . The loss of hydrophobicity was caused by defects in the surface microstructures, a decrease in the hydrophobic ―CH3 groups, and an increase in the hydrophilic ―OH groups on the surfaces. To avoid the decrease in the hydrophobicity of the prepared superhydrophobic surface, a simple and efficient heat treatment method was adopted to restore its hydrophobicity. After heat treatment at 200°C, the rolling angle of the aged surface was restored to 4.6 o with a contact angle of 161.5 o . This recovery is mainly attributed to the decrease in the content of the ―OH on the rubber surface during the heat treatment. The results also show the sample surface irradiated with a laser fluence of 10.0 J/cm 2 has better anti-aging performance and self-healing properties due to the larger particles and a more distinct micro-nano hierarchical structures, providing a smaller actual illumination area and a larger heating area in the aging and heat treatment process.